Fertigation of arugula crops grown in saline soils - Torres, Márcia Batista; Lima, Antonio Fábio da Silva; Souza, Maria Vanessa Pires de; Sousa, Alan Bernard de Oliveira; Taniguchi, Carlos Alberto Kenji; Silva, Alexsandro Oliveira da (Comunicata Scientiae, 2024)
Arugula is a leafy vegetable that has been standing out in terms of consumption due to its nutritional content. The crop has low tolerance to water salinity (ECw), and information on the management of fertilization in saline environments is scarce. In this context, this study aimed to analyze the nutritional aspects of arugula under different soil salinity levels and fertilization doses via fertigation. The experiment was conducted in a greenhouse during two production cycles in 2021 in a randomized block design and a 4 x 3 factorial arrangement, with four replications. The treatments consisted of four soil salinity levels (ECse = 0.57, 1.3, 2.3, and 3.3 dS m−1) and three doses of a mineral fertilizer based on the recommended fertilization via fertigation (F1 = 100%, F2 = 50%, and F3 = 25%). The contents of N, P, K, Ca, Mg, S, Na, Cu, Fe, Zn, and Mn were evaluated after harvesting. Salinity directly affected the concentration of mineral elements in arugula leaf during the first cycle, mainly Ca, Mg, Zn, and Mn. The fertigation strategy with 100% of the recommended fertilization showed better results than the other doses for N, P, K, and S. In the second cycle, all elements showed a reduction due to the high ECse, mainly the value of 3.3 dS m−1. The fertigation strategy that used 100% of the recommended fertilization promoted higher nutrient accumulation in arugula. The order of nutrient accumulation in arugula leaf was K>N>Ca>S>Mg>P>Fe>Zn>Mn>Cu.